THE EXPANSION OF Merremia peltata (L.) MERRILL IN FRAGMENTED FOREST OF BUKIT BARISAN SELATAN NATIONAL PARK ENHANCED BY ITS ECOPHYSIOLOGICAL ATTRIBUTES - Yansen Yansen; Wiryono Wiryono; Deselina Deselina; Muhammad F. Hidayat; Efratenta K. Depari (SEAMEO BIOTROP, 2015)
Forest opening and fragmentation may affect the composition of vegetation by permitting the expansion or domination of one or two species in the area. This study found that , an invasive climbing creeping Merremia peltata/species, has dominated some area of Bukit Barisan Selatan National Park (BBSNP). Domination of this species was favoured by forest fragmentation, indicated by the significantly higher number of individuals of in the open M. peltataarea than in intact forest. The ecophysiological characters of support the ability of this species to become a M. peltatastrong invader. As the expansion of this species may negatively affect the biodiversity and vegetation health, the application of appropriate ecological approaches to control the domination of in the conservation area is M. peltatanecessary.